2017
DOI: 10.21037/mhealth.2017.08.06
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the mHealth technology in improvement of healthy behaviors in an elderly population—a systematic review

Abstract: Demographic changes in the 21st century, increased population of the elderly and high prevalence of related diseases call for new healthcare strategies that can change the behavior and lifestyle of elderly individuals. Innovative information and communication technology, such as mobile health (mHealth), can play a significant role. The present study was conducted aiming to assess the effectiveness of mHealth in improving health behaviors among an elderly population. This paper presents a systematic review invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
134
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(151 citation statements)
references
References 22 publications
8
134
1
8
Order By: Relevance
“…This was related to the results of a systematic review on the effects of remote patient monitoring among health failure patients, in which 15 out of 19 were elderly patients [36]. Changizi and Kaveh [37] also found that mHealth interventions were effective in improving healthy behaviors in persons aged over 60, showing that the interventions were statistically significant in improving disease prevention, lifestyle changes, and cardiovascular disease management. These results support the argument that mobile phone-based interventions are feasible and can benefit the health outcomes of older HF patients.…”
Section: Discussionmentioning
confidence: 88%
“…This was related to the results of a systematic review on the effects of remote patient monitoring among health failure patients, in which 15 out of 19 were elderly patients [36]. Changizi and Kaveh [37] also found that mHealth interventions were effective in improving healthy behaviors in persons aged over 60, showing that the interventions were statistically significant in improving disease prevention, lifestyle changes, and cardiovascular disease management. These results support the argument that mobile phone-based interventions are feasible and can benefit the health outcomes of older HF patients.…”
Section: Discussionmentioning
confidence: 88%
“…In the present review, which unlike that of Muellmann et al (2018) focused on mobile interventions and included three types of behaviors (PA, SB, and sleep), only 8 of the studies included long-term follow-up data, with periods of follow-up ranging from 3 (four studies), 6-8 (three studies), to 24 (one study) months. In the 12 studies reviewed by Changizi and Kaveh (2017), the average duration of the interventions was approximately 24 weeks, but no information about long-term follow-up or sustainability of effects was provided.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Muellmann et al (2018) reached the same conclusion in their review of eHealth PA interventions for older adults. Whether theory guided intervention development in the studies reviewed by Changizi and Kaveh (2017) was not clear. Additionally, an important step in identifying effective interventions is to design them in a way that allows for evaluation of different intervention components and identification of specific behavior change techniques thought to drive behavior change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such apps are intended to promote individuals' health-related behaviors such as sleep, diet, physical activity, and mental health, as well as adherence to medication. Mobile health (m-health) can also be useful in disease prevention, lifestyle modification, cardiovascular disease management, and diabetes (18). M-health is therefore a valuable and appropriate tool for the elderly.…”
Section: Discussionmentioning
confidence: 99%